Castleman’s Disease Mimetizing Pancreatic Tumor - Apodaca-Torrez, Franz Robert; Filho, Benedito Herani; Beron, Reinaldo Isaacs; Goldenberg, Alberto; Goldman, Suzan Menasce; Lobo, Edson José (JOP. Journal of the Pancreas, 2012)
<!--[if gte mso 9]> Normal 0 14 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> <span style="font-size: 8.0pt; line-height: 115%; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; line-height: 115%; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Angiofollicular lymph node hyperplasia or Castleman’s disease is a rare clinical condition. Knowledge about etiology and physiopathology; and treatment management as well are yet to be defined. Unicentric presentation of this disease affecting single lymph nodes in the mediastinum seems to be the most common presentation. Castleman’s disease localized in the pancreas topographic area that mimics a pancreatic neoplasm is an even more uncommon event, with available published data of less than 15 cases until now. Case report We present a 64-year-old male patient with a six-month past history of asthenia, adynamia, and lack of general clinical conditions. Imaging studies showed a nodular hypoechoic mass in the pancreatic head. Enucleation of the lesion was performed. Histopathological study revealed unicentric form of Castleman’s Disease. Conclusions Castleman’s disease mimetizing pancreatic tumor is uncommon and it also curses with a difficult preoperative diagnosis. Surgery seems to be the best therapeutic alternative for this disease.